Effect of organic and inorganic fertilizers on nitrogen and potassium uptake and yield of sweet corn grown on an acid soil - Mohd Yusuff, Mohd Taufik; Ahmed, Osumanu Haruna; Wan Yahaya, Wan Asrina; Nik Ab. Majid, Nik Muhamad (Science Publications, 2007)
A field study was carried with the following objectives: (i) To investigate the effect of compost, N, and K fertilizers on selected chemical properties of Bekenu series (Tipik Tualemkuts), and (ii) To investigate the effect of compost, N and K fertilizers on N and K uptake and yield of Masmadu variety cultivated on Bekenu series. Treatments evaluated were: (i) No fertilization (T1), (ii) Hundred percent inorganic fertilizer application (T2), (iii) Eighty percent of N fertilizer plus twenty percent of N from compost application (T3), (iv) Sixty percent of N fertilizer plus forty percent of N from compost (T4), and (v) Application of hundred percent compost (T5). The experiment was conducted at the share farm of Universiti Putra Malaysia Bintulu Campus, Sarawak, Malaysia. The experimental design was a randomized complete block design (RCBD) with 4 replications. Nitrogen and K were applied in the forms of urea (46 % N) and muriate of potash (60 % K2O) in split i.e., at 15 days after planting (DAP) and 36 DAP, respectively. At 73 DAP, plants were harvested. The fresh weight of cobs excluding guard rows was recorded. Dry weight (stem and leaves), N, K, Ca, and Mg concentrations were determined by standard procedures. Soil sampling was done before and after fertilization. Soil total N was determined using the Kjeldahl method while exchangeable K, Ca, and Mg were extracted using the double acid method and their concentrations determined using atomic absorption spectrophotometry. Dry ashing method was used for the determination of K, Ca, and Mg concentrations in plant tissues while the Kjeldahl method was used to determine total N in plant tissues. The concentrations multiplied by the oven dried weight of roots and stem provided N, K, Ca and Mg uptake in these plant parts. T2, T3, T4 and T5 affected soil bulk density, CEC, pH, total N, exchangeable K, Ca and Mg. The dry weight of Masmadu leaf was not affected by fertilization and so was N and K uptake in this plant part. T2 was superior to the other treatments in terms of stem dry weight and cob production although the uptake of N and K in Masmadu stem under T2 was statistically not different from T3, and T4. Isotopic studies to quantify the amount of N and K contributed by compost in relation N and K uptake and yield may help to conclusively explain why T2 was superior to T3 and T4 in particular.